A direct method for assessment effect of TMD's parameters on seismically excited structures by evolutionary algorithms. (1st January 2011) - Ghanbarpour, Yavar
In this paper, an efficient approach based on multi-objective genetic algorithms (MGA) is proposed to minimise the response of MDOF structures. The optimal design parameters of TMD in terms of damping coefficients and spring constant corresponding of TMD are determined through minimisation of two performance index contain inter-story drifts and acceleration of floors for safety and habitability respectively under one-dimensional earthquake loading simulated by passing a Gaussian white noise process through a second order filter yielding which is well-known Kanai-Tajimi spectrum. For further numerical verification of proposed method, a ten-story shear building implemented with TMD is analysed and the results are compared with other established methods. The results show the efficiency of this method for obtaining optimal parameters of TMD in comparison with other methods. The other advantage of this method is attaining better performance of designed TMD under both of near-field and far-field earthquakes.